Full-scale testing of low adhesion effects with small amounts of water in the wheel/rail interface - Buckley-Johnstone, Luke; Trummer, Gerald; Voltr, Petr; Six, Klaus; Lewis, Roger (Elsevier Science BV, 2020)
Low adhesion in the wheel/rail contact can be caused by small amounts of water combining with iron oxides. This happens in light rain or at dew point. In small-scale tests, ultra-low adhesion (<= 0.05) has not been maintained. The aim here was to see if the mechanism could be realized at a larger scale. Sustained ultra-low adhesion was achieved when water was applied constantly to the wheel/rail contact at a rate of 25 mu L/s. In these conditions wear debris and oxide was clearly visible in the contact band. Creep force data has been generated that can now be used to inform wheel/rail contact models and multi-body dynamics simulations of train behaviour with a view to developing mitigation.
Testování jevů nízké adheze v plném měřítku s malým množstvím vody v kontaktu kolo-kolejnice
Keywords: low adhesion; wheel/rail interface; full-scale tests; wet-rail syndrome; nízká adheze; kontakt kolo-kolejnice; zkoušky v plném měřítku; mokré kolejnice